The concept of Homeland and Fatherland in the poetry of Sergei Yesenin and Erkin Vakhidov (Eurasian Journal of Learning and Academic Teaching, 2023)
This article examines the analysis of the works of famous poets such as Erkin Vakhidov and the Russian poet Sergei Yesenin. Similarities are often observed mainly in works of fiction and poetry in the interpretation of the concepts of Homeland and Fatherland.